A comprehensive, multi-level investigation of the implementation of a novel digital substance misuse intervention, Breaking Free Online: conceptualising implementation processes within services using the MRC framework and health psychology theory. - Stephanie Dugdale; Martha Dalton (Frontiers Media S.A., 2015)
Background: Medical Research Council (MRC: Craig et al., 2008) guidelines outline the importance of a cycle of continual development, feasibility testing, outcomes evaluation and implementation analysis when creating and evaluating complex interventions. However the implementation analysis phase of the intervention creation and evaluation process is often neglected within behavioural change intervention development research. This is problematic as the implementation process is important when developing and evaluating innovative interventions that could be seen to be 'disruptive', such as digital health interventions, in order to be able to effectively translate these interventions into real-world, standard clinical practice. One such digital health innovation is Breaking Free Online (BFO), a technology-enhanced treatment and recovery programme for substance misuse and comorbid mental health difficulties ('dual diagnosis'), which contains theoretically defined, evidence-based psychosocial intervention techniques informed by cognitive behavioural therapy and mindfulness principles. Following the MRC guidelines, a process of development, feasibility testing and clinical outcomes evaluation has taken place using BFO, with findings suggest that the programme is effective in reducing substance use and social impairment and improving depression, anxiety and overall quality of life (Elison et al., 2013, 2014, 2015a, 2015b). Currently BFO is being implemented in services across the UK including Crime Reduction Initiatives (CRI), a health and social care charity and one of the largest substance misuse treatment providers in the UK. Aim: This series of studies, informed by the principles set out in the MRC guidelines, set out to investigate implementation processes of BFO within CRI and the subsequent normalisation of the programme throughout this real-world healthcare service, in order to inform further developments to the programme. Theories and models from within the disciplines of health psychology and implementation science were used to conceptualise these processes. Methods: Semi-structured qualitative interviews were conducted with staff, peer mentors and service users to investigate initial diffusion and subsequent normalisation of BFO within CRI, and the impact of BFO on peer mentors' own substance misuse recovery journeys. Thematic analyses were conducted, and models derived from health psychology and implementation science used to conceptualise implementation processes from an organisational level. Further analyses using Interpretative Phenomenological Analysis (IPA) expanded investigation down to the level of individual people within CRI, and the role of peer mentors delivering the programme within the organisation. Results: 'Diffusion of innovation theory' conceptualised initial implementation and diffusion of BFO throughout CRI. Although there were perceived barriers to implementation, such as lack of IT equipment, anxieties around staff and service user IT skills and the impact on staff's professional roles, intentions to continue using BFO were reported. Analyses investigating continued implementation processes of the programme used 'normalisation process theory' to demonstrate how a process of normalisation of the programme is underway following initial diffusion. Findings suggested that staff were beginning to take greater 'ownership' of BFO since it was initially introduced into the organisation, and that the programme was influencing changes to work-role responsibilities in delivering BFO. Data using the 'trans-theoretical model' also indicated that peer mentors benefited from implementing BFO to support others and assist their own recovery maintenance. Conclusion: Whilst the principal focus must always be on establishing clinical effectiveness when developing and evaluating complex behaviour change interventions, such as digital interventions, implementation process analysis is also key. This analysis is important in order for interventions to be translated into real-world outcomes, as without considering implementation, the potential impact of an intervention is compromised. This research has implications for the valuable roles of health psychology models and implementation science theories in understanding the complex processes of implementation of digital health innovations such as BFO.